THE ANALYSIS OF THE EPIZOOTIC SITUATION OF INFECTIOUS DISEASES OF PIGS IN UKRAINE - Якубчак, О. М.; Обштат, С. В.; Муковоз, В. М.; Карпуленко, М. С.; Гавриленко, О. С. (Scientific Progress & Innovations, 2014)
The article analyzed the statistical data in comparative historical aspect of Veterinary reporting in Ukraine of infectious diseases of pigs in period from 1999 by 2013. The most common diseases in Ukraine is colibacillosis, salmonellosis and leptospirosis, that require application preventive measures. The high intensity of epizootic process of infectious diseases was revealed and characterized of a common incidence is more than 1% and of epizootic index, that varies between 0,62-1,00. The analyzed data indicate about danger aforementioned diseases and the need for a detailed study of the characteristics of their occurrence.